2020
DOI: 10.23887/jere.v4i3.26277
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Deixis Used by Foreign and Local English Teachers in Vocational High School

Abstract: This study aims to analyze the types of deixis by using Levinson’s theory, find out the dominant types of deixis, and the reasons behind the uses of deixis by foreign and local English teachers. The study used a qualitative method particularly a case study. The data sources of this study were the foreign and local English teachers’ utterances. The data were obtained through a classroom observation and interview technique. The data were analysed using Miles and Hubermans’s interactive model. The findings showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Besides, other relevant studies compared person deixis among two languages and English teachers, where the results showed that English teachers were dominant in using person deixis (Novianty, Saleh , Sukmawati, 2018;Mayori, Putra, Suarnajaya , 2020). In line with those studies, Hong-mei, Dan, Dan-wu (2016) also discussed about person deixis, but they did not compare.…”
mentioning
confidence: 95%
“…Besides, other relevant studies compared person deixis among two languages and English teachers, where the results showed that English teachers were dominant in using person deixis (Novianty, Saleh , Sukmawati, 2018;Mayori, Putra, Suarnajaya , 2020). In line with those studies, Hong-mei, Dan, Dan-wu (2016) also discussed about person deixis, but they did not compare.…”
mentioning
confidence: 95%